Consumer attitudes towards Instagram advertisements in Egypt: The role of the perceived advertising value and personalization - Hazem Rasheed Gaber (Taylor & Francis Group, 2019)
This article investigates the factors that affect consumers’ attitudes towards Instagram advertisements in Egypt. Furthermore, it studies the effect of consumers’ attitudes towards these advertisements on the development of their attitudes towards brands. An online questionnaire was used to collect data from 412 Instagram users in Egypt. The results suggest that the level of consumers’ perception of informativeness, entertainment, credibility and lack of irritation in the Instagram advertisements is strongly related to their attitudes. Moreover, the results confirm the positive effect of consumers’ attitudes towards Instagram advertisements on their attitudes towards the advertised brands. The current study contributes theoretically by presenting the factors that can make consumers hold favourable attitudes towards advertising on their Instagram accounts. This expands the focus of the theory of consumers’ attitudes towards advertisements to social media which has largely replaced traditional advertising media. Additionally, this article contributes practically by providing some guidelines for marketers to follow when advertising on Instagram.